Orbit determination for fuel station in multiple SSO spacecraft refueling considering the J2 perturbation - Zhu, Xiaoyu; Zhang, Chengxi; Sun, Ran; Chen, Junli; Wan, Xiangcheng (Aerospace science and technology, 2020)
This paper investigates the orbit determination problem for fuel station (FS) in multiple Sun-Synchronous Orbit (SSO) spacecrafts refueling mission. A novel K-M-N transportation network to solve this general refueling problem is proposed, which contains several FSs with their reusable servicing spacecraft (SSC) and a large number of targets. The proposed network allows the FS drifting in a cooperative rendezvous to reduce the fuel consumption considering the J2 perturbation. Furthermore, one-to-one mode is chosen as the refueling strategy between the FS and the target, which makes it feasible to determine the number and orbit of the FS. In order to achieve such an economical refueling strategy, the problem is formulated as a facility location–allocation (FLA) model, subject to the different demands among targets and the limitation of SSC's capacity. Then, a hybrid Density-Based Spatial clustering algorithm (HDBSCAN) is designed to solve the multi-objective optimization model. Finally, two numerical examples are presented to illustrate the effectiveness and validity of the proposed algorithm.